Transgenic Medaka Identify Embryonic Periods Sensitive to Disruption of Sex Determination. (21st February 2020) - Spirhanzlova, Petra; Trébulle, Pauline; Lallement, Justine; Sébillot, Anthony; Kanamori, Akira; Lemkine, Gregory F.; Tindall, Andrew J.
Abstract : A novel 42sp50‐GFP_ChgH‐GFP transgenic medaka line was developed allowing the identification of female gonadal tissue by fluorescence present in developing oocytes. Fry were exposed to 24‐h pulses of high concentrations of estradiol or dihydrotestosterone at various time points between 0 and 12 day postfertilization to identify developmental time points sensitive to disruption of sex steroid signaling. DHT = dihydrotestosterone; DPF = day postfertilization; E2 = estradiol. Abstract: Gonadal development in medaka ( Oryzias latipes ) is dependent on the synergy between estrogens and androgens. Disruption of steroid hormone levels can lead to ovo‐testis. To determine the sensitive windows for hormonally induced sex reversal in medaka, we developed a novel 42sp50‐GFP_ChgH‐GFP transgenic medaka line, allowing the identification of female gonadal tissue by fluorescence present in developing oocytes. Germinal transgenesis resulted in a stable line exhibiting a strong green fluorescent protein signal constitutively in the ovaries and in the liver in response to estrogens. The sensitivity of this line to disruption of sex determination following 16‐d chronic exposures was in the nanograms per liter range. To identify the developmental period sensitive to exogenous agents, fry were exposed to 24‐h pulses of high concentrations of 17β‐estradiol (E2) or 5α‐dihydrotestosterone (DHT) at various time points between days postfertilization (dpf) 0 and 12. Evaluation of phenotype followed by genotyping at 16 dpf revealed sensitivity to E2 between 1 and 8 dpf as well as 2 periods of susceptibility to DHT between 0 and 1 dpf and 4 and 8 dpf. No phenotypic sex reversal was detected after exposure to DHT or E2 on 11 or 12 dpf. The observed effects persisted to at least 24 dpf. The identified sensitive embryonic time periods for disruption of sex determination will aid future research on sex determination and the development of screening assays using early embryonic life stages. Environ Toxicol Chem 2020;39:842–851. © 2020 SETAC